Subclonal evolution of pulmonary adenocarcinomas delineated by spatially distributed somatic mitochondrial mutations - Kazdal, Daniel; Harms, Alexander; Endris, Volker; Penzel, Roland; Kriegsmann, Mark; Longuespée, Rémi; Winter, Hauke; Schneider, Marc; Stenzinger, Albrecht; Warth, Arne (Lung cancer, 2018)
Objectives - The potential role of cancer associated somatic mutations of the mitochondrial genome (mtDNA) is controversial and still poorly understood. Our group and others recently challenged a direct tumorigenic impact and suggested a passenger-like character. In combination with the known increased mutation rate, somatic mtDNA mutations account for an interesting tool to delineate tumor evolution. Here, we comprehensively analyzed the spatial distribution of somatic mtDNA mutations throughout whole tumor sections of pulmonary adenocarcinoma (ADC). - Materials and methods - Central sections of 19 ADC were analyzed in a segmented manner (11-34 segments/tumor) together with non-neoplastic tissue samples and lymph node metastasis, if present. We performed whole mtDNA sequencing and real-time PCR based quantification of mtDNA copy numbers for all samples. Further, histological growth patterns were determined on H&E sections and the tumor cell content was quantified by digital pathology analyses. - Results - Somatic mtDNA mutations were present in 96% (18/19) of the analyzed tumors, either ubiquitously or restricted to specific tumor regions. Spatial and histological mapping of the mutations enabled the identification of subclonal structures and phylogenetic relations within a tumor section indicating different progression levels. In this regard, lymph node metastases seem to be related to early events in ADC development. There was no concurrence between histological and mtDNA mutation based clusters. However, micropapillary patterns occurred only in tumors with ubiquitous mutations. ADC with more than two ubiquitous mutations were associated with shorter disease-free survival (p < 0.01). - Conclusion - Cancer related mtDNA mutations are interesting candidates for the understanding of subclonal ADC evolution and perspectively for monitoring tumor progression. Our data reveal a potential prognostic relevance of somatic mtDNA mutations.